Finite Element Method For The Solution Of A Time-Dependent Heat-Like Lane-Emden Equation - Uçar, Mehmet Fatih (My University, 2018)
In this study, finite element method (FEM) with Galerkin Formula is applied to find the numerical solution of a time-dependent heat-like Lane-Emden equation. An example is solved to assess the accuracy of the method. The numerical results are obtained for different values (n) of equation. The results indicate that Galerkin method is effectively implemented. It is seen that results are compatible with exact solutions and consistent with other existing numerical methods.
Keywords: Time-dependent Lane-Emden equation; Galerkin method; Heat-type equation; Time-dependent Lane-Emden equation